Vestiges of Ent3p/Ent5p function in the giardial epsin homolog - Feliziani, Constanza (2016)
An accurate way to characterize the functional potential of a protein is to analyze recognized protein domains encoded by the genes in a given group. The epsin N-terminal homology (ENTH) domain is an evolutionarily conserved protein module found primarily in proteins that participate in clathrin-mediated trafficking. In this work, we investigate the function of the single ENTH-containing protein from the protist Giardia lamblia by testing its function in Saccharomyces cerevisiae. This protein, named GlENTHp (for G. lamblia ENTH protein), is involved in Giardia in endocytosis and in protein trafficking from the ER to the vacuoles, fulfilling the function of the ENTH proteins epsin and epsinR, respectively. There are two orthologs of epsin, Ent1p and Ent2p, and two orthologs of epsinR, Ent3p and Ent5p in S. cerevisiae. Although the expression of GlENTHp neither complemented growth in the ent1δent2δ mutant nor restored the GFP-Cps1 vacuolar trafficking defect in ent3δent5δ, it interfered with the normal function of Ent3/5 in the wild-type strain. The phenotype observed is linked to a defect in Cps1 localization and α-factor mating pheromone maturation. The finding that GlENTHp acts as dominant negative epsinR in yeast cells reinforces the phylogenetic data showing that GlENTHp belongs to the epsinR subfamily present in eukaryotes prior to their evolution into different taxa.